PENGARUH LINGKUNGAN KOS-KOSAN TERHADAP MOTIVASI BELAJAR MAHASISWA STAKPN AMBON - Jondri Josias Toisuta (Institut Agama Kristen Negeri (IAKN) Ambon, 2018)
Motivation is the urge to achieve a particular goal. The research aims to determine if there is a Kos-Kosan environmental influence on the learning motivation of students of the National Christian Religious School (STAKPN) Ambon. Research conducted on the STAKPN campus AmbonIn particular, the Department of Christian Religion (PAK) semester II (two), IV (four) and VI (six).This research uses a quantitative type survey approach. The population of the study is all students majoring in Christian religious education Semester II (two), IV (four) and VI (six) who live in Kos-kosan amounting to 120 people. While the sampling of research samples was completed with two techniques namely the first is simple random sampling technique by looking at the table Isach and Michael and secondly using the purposional random sampling technique, then obtained research samples As many as 89 people. The data collection techniques used are questionnaire or questionnaire and non-participation observation.Research Data is analyzed with the help of SPSS type 16.0 Program. Data analysis includes description analysis, test prerequisite analysis and final analysis. Description The analysis of this study is the presentation of maximum value, minimum value, average value (Mean) and standard deviation. The prerequisite analysis test in this study is testing data normality and Linieritas data. The data normality test is done with the formula of Kolmogrov Smirnov and shows normal distribution data. The linierity test is performed and shows there is a linear relationship between the X variables of the cost environment and the variable Y learning motivation. Final analysis testing is conducted including regression test to provide for influence, coefficient of determination to know how much contribution or donations are given in the cost environment variable to learning motivation, and hypothesis testing To contribute significant and positive environmental influences to the motivation of learning. The results of the hypothesis testing proved there was a significant and positive influence marked by the T-count value of the > T table (2,573 > 1,986) and the donations that were given X variables of the cost environment against the Y Motivai variable studied at 0.71 or 7.1% as the rest 92.9% influenced by other variable-varibellsKeyword: cost environment, learning motivation